A study of ‘China English’ and its linguistic features / Deng Yun - Deng, Yun (2012)
Based on Kachru’s theory of World Englishes, namely the Three Concentric Circles Model, this study will link the concept naturally to the English which is used in the Chinese context and brings it into primarily two stages of nativization of English in contemporary China: ‘Chinglish’ and ‘China English’. After the comprehensive analysis of the differences between ‘Chinglish’ and ‘China English’, the study aims to make a new definition of the term ‘China English’ in the domain of World Englishes. Following that, the researcher would exemplify the linguistic features of ‘China English’ at three levels, viz lexis, syntax and discourse. The data collected are corpus-based and textual analysis-combined. The corpus of 100 Chinese borrowings from eight dictionaries in Cannon’s study (1988) developed by Yang(2009) was adopted in the present study. Forty 300-word compositions written by undergraduate students were collected from one college in the southwest of mainland China as the source of text analysis. Subsequently, the findings state that ‘China English’ is properly defined as a performance variety with ‘Normative English’ as its core used by the Chinese people. Also, it is colored with some linguistic features presented with reference to phonology, lexis, syntax and discourse. Those linguistic features inevitably influenced by both Chinese language itself and Chinese thinking model, which is especially appropriate for presenting those perspectives peculiar to the Chinese culture.